2018
DOI: 10.1017/wet.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Control of Photosystem II– and 4-Hydroxyphenylpyruvate Dioxygenase Inhibitor–Resistant Palmer Amaranth (Amaranthus palmeri) in Conventional Corn

Abstract: Palmer amaranth, a dioecious summer annual weed species, is the most troublesome weed in agronomic crop production systems in the United States. Palmer amaranth resistant to photosystem (PS) II- and 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors is of particular concern in south central Nebraska. The objectives of this study were to determine the effect of PRE followed by POST herbicide programs on PS II- and HPPD-inhibitor-resistant Palmer amaranth control, crop yield, and net economic return in conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…Similar Palmer amaranth control (95-100%) with acetochlor/atrazine has been reported in the literature (Janak & Grichar, 2016). Chahal et al (2018) reported 90% Palmer amaranth control and 82% biomass reduction 28 DA POST from saflufenacil/dimethamid-P fb diflufenzopyr/dicamba. Hauver, Chahal, Watteyne, and Jhala (2017) reported 93% control of Palmer amaranth with clopyralid/acetochlor/mesotrione.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar Palmer amaranth control (95-100%) with acetochlor/atrazine has been reported in the literature (Janak & Grichar, 2016). Chahal et al (2018) reported 90% Palmer amaranth control and 82% biomass reduction 28 DA POST from saflufenacil/dimethamid-P fb diflufenzopyr/dicamba. Hauver, Chahal, Watteyne, and Jhala (2017) reported 93% control of Palmer amaranth with clopyralid/acetochlor/mesotrione.…”
Section: Discussionsupporting
confidence: 84%
“…Chahal et al. () reported 90% Palmer amaranth control and 82% biomass reduction 28 DA POST from saflufenacil/dimethamid‐P fb diflufenzopyr/dicamba. Hauver, Chahal, Watteyne, and Jhala () reported 93% control of Palmer amaranth with clopyralid/acetochlor/mesotrione.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Palmer amaranth from Nebraska is resistant to atrazine and HPPD‐inhibiting herbicides applied alone, these herbicides can be tank mixed with different site of action herbicides for effective Palmer amaranth control (Chahal et al, 2018). However, it is important to adopt an integrated Palmer amaranth management approach that includes the use of a PRE herbicides followed by a POST herbicide program, rotation of herbicides with distinct sites of action, crop rotation, rotation of herbicide‐resistant cultivars, tillage, and harvest weed seed control methods to mitigate the evolution and spread of multiple herbicide‐resistant weeds including Palmer amaranth (Chahal et al, 2018; Ganie et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Esto, concuerda con investigaciones desarrolladas por centros de investigación argentinos, que evalúan la capacidad de resistencia a condiciones adversas de clima y suelo sobre las potencialidades alimentarias del amaranto y la resistencia a los efectos del cambio climático en condiciones de difícil adaptabilidad [41], [42].…”
Section: Clima Para Amarantounclassified